2012
DOI: 10.1542/hpeds.2012-0048
|View full text |Cite
|
Sign up to set email alerts
|

The Strategic Planning Committee Report: The First Step in a Journey to Recognize Pediatric Hospital Medicine as a Distinct Discipline

Abstract: The field of pediatric hospital medicine (PHM) has experienced phenomenal growth over the past decade. Academic contributions by pediatric hospitalists include the creation of PHM core competencies,1 national collaborative PHM networks for both research (the Pediatric Research in Inpatient Settings network2) and quality improvement (the Value in Inpatient Pediatrics network3), a robust and well-attended annual scientific meeting,4 and an increasing number of divisions or sections of PHM in pediatric department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…26 These are important considerations as program directors solidify fellowship goals in response to certification options. 27 This study has several limitations. Although the authors attempted to identify all PHM fellowship graduates before 2014, there is potential for sampling bias.…”
Section: Discussion/conclusionmentioning
confidence: 92%
“…26 These are important considerations as program directors solidify fellowship goals in response to certification options. 27 This study has several limitations. Although the authors attempted to identify all PHM fellowship graduates before 2014, there is potential for sampling bias.…”
Section: Discussion/conclusionmentioning
confidence: 92%
“…In 2012, the STP shared the results of Strengths-Weaknesses-Opportunities-Threats analyses-but did not issue a recommendation. 17 The following year, a National PHM Leaders Conference was held to consider the various options. Participants concluded that the best path forward was to pursue subspecialty certification with a requirement for 2 years of fellowship (after a time-limited period for practice pathway eligibility).…”
Section: Path To Subspecialty Statusmentioning
confidence: 99%
“…While not yet accredited by the ACGME, fellowships are becoming more common and stronger in the training in research and clinical management they provide. 29 The new model of specialty tracking during residency also provides an opportunity for trainees interested in hospital medicine to obtain sub-specialized training, including peri-operative care. 29 Finally, with the increased prevalence of children with complex chronic conditions, 1,2 there is greater need for specific training to care for these children.…”
Section: Current Challenges and Issues For Surgical Comanagement In Tmentioning
confidence: 99%
“…29 The new model of specialty tracking during residency also provides an opportunity for trainees interested in hospital medicine to obtain sub-specialized training, including peri-operative care. 29 Finally, with the increased prevalence of children with complex chronic conditions, 1,2 there is greater need for specific training to care for these children. Peri-operative management is an essential component of care of the complex child, since these children tend to have more technology than non-complex children.…”
Section: Current Challenges and Issues For Surgical Comanagement In Tmentioning
confidence: 99%